Influence of beech particle size used in surface layer on bending strength of three-layer particleboard - Medved, Sergej (Zbornik gozdarstva in lesarstva, 2003)
It is well known that wood species and particle size used influence the bending strength of the three-layer particleboard. The purpose of this research was to determine how the size of beech (Fagus sylvatica L.) particlesinfluences the bending strength of the three-layer particleboard, where size of particles used was altered in surface layer only. Beech wood particles of five different sizes were used and blended with UF adhesive. The results show that the bending strength of boards increases with increasing particle specific surface area, increasing surface layer compaction ratio and surface layer density, while bending strength decreases with increasing surface covered with adhesive.
Keywords: bukov les; iverne plošče; upogibna trdnost; velikost delcev